Challenges of controlling the rotation of virtual objects with variable grip using force-feedback gloves - Bonfert, Michael; Hübinger, Maiko; Malaka, Rainer (Frontiers in Virtual Reality, 2023)
Some virtual reality (VR) applications require true-to-life object manipulation, such as for training or teleoperation. We investigate an interaction technique that replicates the variable grip strength applied to a held object when using force-feedback gloves in VR. We map the exerted finger pressure to the rotational freedom of the virtual object. With a firm grip, the object's orientation is fixed to the hand. With a loose grip, the user can allow the object to rotate freely within the hand. A user study (N = 21) showed how challenging it was for participants to control the object's rotation with our prototype employing the SenseGlove DK1. Despite high action fidelity, the grip variability led to poorer performance and increased task load compared to the default fixed rotation. We suspect low haptic fidelity as an explanation as only kinesthetic forces but no cutaneous cues are rendered. We discuss the system design limitations and how to overcome them in future haptic interfaces for physics-based multi-finger object manipulation.